Genome analysis of Salmonella enterica serovar Typhimurium bacteriophage L, indicator for StySA (StyLT2III) restriction-modification system action. Issue 1 (26th January 2021) - Zaworski, Julie; McClung, Colleen; Ruse, Cristian; Weigele, Peter R; Hendrix, Roger W; Ko, Ching-Chung; Edgar, Robert; Hatfull, Graham F; Casjens, Sherwood R; Raleigh, Elisabeth A
Abstract: Bacteriophage L, a P22-like phage of Salmonella enterica sv Typhimurium LT2, was important for definition of mosaic organization of the lambdoid phage family and for characterization of restriction-modification systems of Salmonella . We report the complete genome sequences of bacteriophage L cI – 40 13 – am 43 and L cII – 101; the deduced sequence of wildtype L is 40, 633 bp long with a 47.5% GC content. We compare this sequence with those of P22 and ST64T, and predict 72 Coding Sequences, 2 tRNA genes and 14 intergenic rho-independent transcription terminators. The overall genome organization of L agrees with earlier genetic and physical evidence; for example, no secondary immunity region ( immI : ant, arc ) or known genes for superinfection exclusion ( sieA and sieB ) are present. Proteomic analysis confirmed identification of virion proteins, along with low levels of assembly intermediates and host cell envelope proteins. The genome of L is 99.9% identical at the nucleotide level to that reported for phage ST64T, despite isolation on different continents ∼35 years apart. DNA modification by the epigenetic regulator Dam is generally incomplete. Dam modification is also selectively missing in one location, corresponding to the P22 phase-variation-sensitive promoter region of the serotype-converting gtrABC operon. The number of sites for SenLTIII (StySA) action may account for stronger restriction of L (13 sites) than of P22 (3 sites).